Peran Word Of Mouth Memediasi Pengaruh Social Media Marketing Dan Brand Image Terhadap Keputusan Mahasiswa Memilih Lembaga Pelatihan Kerja (LPK) PPLP Dhyana Pura Badung - Lilyk Dwi Astuti, Rai; Dewi, Luh Komang Candra; Kartika Yuni, L.K Herindiyah (Relasi : Jurnal Ekonomi, 2024)
This research aims to determine and analyze the role of word of mouth in mediating the influence of social media marketing and brand image on students’ decisions to choose LPK PPLP Dhyana Pura in Badung. The population in this study was 539 students of the PPLP Dhyana Pura Job Training Institute (LPK) for the 2023/2024 academic year. Samples were determined using the Slovin formula with a sample size of 100 samples. Data collection in this research used questionnaires with SPSS data analysis techniques. Researchers used three types of variables. The validity test is carried out using the SPSS program where an instrument is said to be valid if r ≥ 0.30 and if the value is smaller it is considered invalid so that the variable in question can be eliminated. To calculate the reliability value, use a Cronbach alpha value above 0.6. The results of this research show that social media marketing has a positive and significant influence on student decisions, brand image has a positive and significant influence on student decisions, social media marketing has a positive and significant influence on word of mouth, brand image has a positive influence on word of mouth, word of mouth has an influence positive and significant on student decisions. Social media marketing and brand image indirectly have a positive influence on student decisions through word of mouth mediation.